(untitled) (Advancements in Homeopathic Research, 2022)
Prenatal factors as determinants of health and illness are probably the most interesting areas of research by the affirmed mainstream. The new emphasis on nurture (environment) controlling the nature (genes) [Epigenetics] focuses special attention on the importance of the maternal environment in foetal development. In addition to the established role of maternal physiology, it is now recognised that maternal behaviours and emotions profoundly impact the child’s physical development, behavioural characteristics and even its level of intelligence. This article is an attempt to understand the importance of detailed history taking of intra uterine life and how it can help in understanding the disease at present and also help in prescribing when all the paths to find the similimum fails.